Vertical Production Networks: Evidence from France - Laurent Wagner; Laurence Nayman; Michel Fouquin (Kiel Institute for the World Economy (IfW), 2007)
This paper investigates the determinants of intra-firm trade of multinational firms located in France, using data on French companies. Results on the vertical pattern of production networks differ according to the affiliates? location. Lower wage and transportation costs in the developing countries increase, as expected, the vertical segmentation of production. In the developed countries, lower trade and unit wage costs, and hence, a strong and positive labour productivity matter a lot in explaining French MNCs? preferences. Among the other variables of interest, partnership and market potential have been given special attention. The results substantiate a mix of vertical and horizontal FDI, mainly when we separate out capital intensive from labour intensive intermediate products.
Keywords: L1; F1; F23; 330; Multinational Firms; Intra-firm Trade; Intermediate Products; Vertical Production Networks; Horizontal FDI